2006
DOI: 10.1016/j.icesjms.2006.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting catch per unit effort data to assess the status of individual stocks and communities

Abstract: Despite being one of the most common pieces of information used in assessing the status of fish stocks, relative abundance indices based on catch per unit effort (cpue) data are notoriously problematic. Raw cpue is seldom proportional to abundance over a whole exploitation history and an entire geographic range, because numerous factors affect catch rates. One of the most commonly applied fisheries analyses is standardization of cpue data to remove the effect of factors that bias cpue as an index of abundance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
312
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(320 citation statements)
references
References 51 publications
1
312
0
7
Order By: Relevance
“…However, differences between surveys indicated that spillover did not occur consistently. This inconsistency may be related to differences in abundance (Harmelin et al 1995) or catchability (Maunder et al 2006) of the species due to seasonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences between surveys indicated that spillover did not occur consistently. This inconsistency may be related to differences in abundance (Harmelin et al 1995) or catchability (Maunder et al 2006) of the species due to seasonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…Hilborn and Walters 1992;Punt et al 2000;Harley et al 2001;Aires-da-Silva et al 2008). The second hypothesis also relates to the fact that catchability may change over time with changing fishing practices (see Maunder et al 2006 for a review). If fishers actively avoid catching elephant fish, catchability will decrease, resulting in a hyper-depleted index of abundance (Hilborn and 1975(Hilborn and 1980(Hilborn and 1985(Hilborn and 1990(Hilborn and 1995 Walters 1992).…”
Section: Cpue Standardisationmentioning
confidence: 99%
“…Catch composition was also assessed based on sub-sampling from the catches of fishermen at the landing sites (Campos et al 1994;Maunder et al 2006).…”
Section: Reef Fishery Assessmentmentioning
confidence: 99%